PENGARUH GANGGUAN PRIBADI, GANGGUAN EKSTERN, GANGGUAN ORGANISASI DAN AUDIT TENURE TERHADAP INDEPENDENSI AUDITOR (Studi Empiris Pada BPK RI Perwakilan Provinsi Riau) - Syaputra, Haizil Adam; Rasuli, M; Kurnia, Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to determine the effect of personal disturbance, external disturbance, organizational disturbance and audit tenure on the the auditor’s independence . (Empirical Studied In BPK RI Of Riau Province). Population of the research is auditor in officers BPK RI of Riau Province. Sampling technique is used sampel jenuh with all population was be sample . Hypotesis test used in this research was statistical t-test. Data analysis techniques used in this research was multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 17.0 for Windows as data processing software program. Results of hypothesis test using statistical t-test showed the significant value of personal disturbance that H1 and the eksternal disturbance that H2 accepted. the organizational disturbance that H3 and the audit tenure that H4 rejected. The results showed personal disturbance and external disturbance has effect on auditor’s independence. While organizational disturbance and audit tenure hasn’t effect on auditor’s independence.Keywords :Personal Disturbance, External Disturbance, Organizational Disturbance, Audit Tenure and The Auditors’ independence